Direct Alloying Steel with Chromium by Briquettes Made from Chromite Ore, Mill Scale, and Petroleum Coke. Issue 5 (31st October 2016) - Hu, Xianfeng; Sundqvist Ökvist, Lena; Eriksson, Johan; Yang, Qixing; Björkman, Bo
Abstract : In this work, the effectiveness of using briquettes made from chromite ore, mill scale, and petroleum coke for direct chromium alloying is tested by induction furnace trials carried out in three different scales. The experimental results show that steel scrap can be alloyed with chromium by the chromite ore in the briquettes and the Cr yield from the chromite ore increases with the increase in mill scale addition to the briquettes: the more mill scale is added to the briquettes, the lower the mass ratio of Cr to (Cr + Fe) would be, leading to a higher Cr yield from the chromite ore. Specifically, the maximum Cr yield from the chromite ore is 99.9% when the mass ratio of Cr to (Cr + Fe) in the briquettes is 0.05, and being 93.0% when the ratio is 0.10. However, when the ratio of Cr to (Cr + Fe) in the briquettes reaches 0.20, the maximum Cr yield is only 67.1%. The reduction of chromite ore under the present experimental conditions is promoted by a solid‐state reduction mechanism. Abstract : Induction furnace trials in three different scales are carried out to investigate the effect of using briquettes made from chromite ore, mill scale, and petroleum coke for directly alloying steel with chromium. It is found that a higher Cr to (Cr + Fe) mass ratio in the briquette(s) leads to a higher Cr yield in the steel.